1999
DOI: 10.1038/12433
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef mediates lymphocyte chemotaxis and activation by infected macrophages

Abstract: Infection of macrophage lineage cells is a feature of primate lentivirus replication, and several properties of primate lentiviruses seem to have evolved to promote the infection of macrophages. Here we demonstrate that the accessory gene product Nef induces the production of two CC-chemokines, macrophage inflammatory proteins 1alpha and 1beta, by HIV-1-infected macrophages. Adenovirus-mediated expression of Nef in primary macrophages was sufficient for chemokine induction. Supernatants from Nef-expressing mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
264
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(278 citation statements)
references
References 52 publications
11
264
2
Order By: Relevance
“…Similar to our findings with M-CSF, MIP-1␣ production by HIV-1-infected MDM is also dependent on viral replication (27,28), but it is not specific for HIV-1. Intriguingly, it has recently been shown that production of MIP-1␣, but not M-CSF, is regulated by the HIV-1 nef protein (34). A role for HIV accessory proteins in the regulation of M-CSF production has yet to be defined and is currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings with M-CSF, MIP-1␣ production by HIV-1-infected MDM is also dependent on viral replication (27,28), but it is not specific for HIV-1. Intriguingly, it has recently been shown that production of MIP-1␣, but not M-CSF, is regulated by the HIV-1 nef protein (34). A role for HIV accessory proteins in the regulation of M-CSF production has yet to be defined and is currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Nef is a 27-kDa protein that is produced early during infection and exerts multiple functional activities. The expression of Nef induces the secretion of CC-chemokines MIP-1 and MIP-1 by infected macrophages (Swingler et al, 1999). These chemokines may help to recruit T lymphocytes at the site of infection by chemotaxis.…”
Section: Macrophage-t Cell Interplay and Hiv-1 Activationmentioning
confidence: 99%
“…These chemokines may help to recruit T lymphocytes at the site of infection by chemotaxis. Moreover, T lymphocytes are activated by a soluble factor released by Nef-expressing macrophages, favouring HIV-1 replication (Swingler et al, 1999). Further studies by the same laboratory showed that CD40L stimulation of macrophages also leads to the release of a factor that induces T lymphocytes to support the replication of an X4 strain of HIV-1 without any other extrinsic stimulation (Swingler et al, 2003).…”
Section: Macrophage-t Cell Interplay and Hiv-1 Activationmentioning
confidence: 99%
“…The lymphocyte chemotaxis assay was performed using 96-well microchemotaxis chambers (NeuroProbe, Gaithersburg, MD) as previously described (28). The MACS magnetic cell separation system was used to isolate CD8 ϩ T cells from fresh PBMCs taken from healthy individuals.…”
Section: Lymphocyte Chemotaxis Assaymentioning
confidence: 99%